2002
DOI: 10.1139/w01-131
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a fibrolytic enzyme preparation from Trichoderma longibrachiatum on the rumen microbial population of dairy cows

Abstract: The effects of supplementing a dairy cow diet with incremental levels of a fibrolytic enzyme preparation (preparation B) from Trichoderma longibrachiatum on the rumen microbial population were investigated. Two cows fitted with rumen cannulae were each fed a diet containing barley-based concentrate (52%), maize silage (29%), and chopped alfalfa hay (19%), supplemented with 0, 1, 2, 5, or 10 L of preparation B per tonne of dry matter (DM). Preparation B stimulated numbers of total viable bacteria in a quadratic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
109
1
8

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(125 citation statements)
references
References 18 publications
7
109
1
8
Order By: Relevance
“…Nsereko et al (6) suggested that exogenous enzymes could increase fiber degradation through a hydrolytic action resulting in more effective rumen fermentation. Tang et al (30) suggested that in vitro GP variables usually reflect the characteristics of the fermentation process.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nsereko et al (6) suggested that exogenous enzymes could increase fiber degradation through a hydrolytic action resulting in more effective rumen fermentation. Tang et al (30) suggested that in vitro GP variables usually reflect the characteristics of the fermentation process.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 180 bottles (three bottles for each ration in addition to three bottles for each enzyme in three different runs with three bottles as blanks (rumen fluid only)) were incubated for 72 h. The technique of Theodorou et al (16) was used for measuring the pressure of gas produced at 2, 4,6,8,10,12,24,36,48, and 72 h of incubation employing a pressure transducer to measure gas from incubations in 120-mL gas-tight culture bottles. Gas accumulated in the headspace of the bottle as the fermentation proceeded was measured with a digital manometer (Extech Instruments, Waltham, MA, USA).…”
Section: In Vitro Incubationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect may be similar to that reported for direct-fed microbials and fermentation extracts (Varel et al 1993;Newbold 1995). Nsereko et al (2002) added various levels of an enzyme product from Trichoderma longibrachiatum to the diet of dairy cows and reported an increase in total viable rumen bacteria. Most of this increase was accounted for by increases in bacterial species that use cellobiose or glucose.…”
Section: Stimulation Of Rumen Microbial Populationsmentioning
confidence: 99%
“…This lack of effect of enzyme treatment on DML following in vitro fermentation has been recognised by others (Colombatto et al 2003) and may be a result of increased microbial biomass. Total bacterial numbers in ruminal fluid have been seen to increase with increasing enzyme levels (Nsereko et al 2002), and since DML in this experiment was in fact apparent DML, due to microbial biomass adhering to the residue, an increase in microbial mass due to enzyme treatment is conceivable.…”
Section: * Significant Quadratic Response (P0·05)mentioning
confidence: 62%